2019
DOI: 10.24252/bio.v7i2.9847
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Insight the Prediction of Chlorogenic Acid in Coffee through Cyclooxygenase-2 (COX2) Interaction

Abstract: Inflammation was signs of pathological or abnormality in tissue to give an alert as a trouble signal to the system. Therapeutic using NSAIDs has some side effects. This research explored the potential role of chlorogenic acid as natural therapeutic compound to inhibit the inflammation target such as COX-2 by interaction model. The research method used in this study was the molecular docking approach, which binds ligand and protein. Protein data provided by Protein Data Bank (ID: 6cox) while, chlorogenic acid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
9
0
6
Order By: Relevance
“…Inflammation that occurs in the body is correlated with inflammatory mediators such as COX-2. COX-2 has the function of initiating and maintaining physiological conditions during inflammation [11]. Compare to affinity character between chlorogenic acid and COX-2 in this research indicated that interaction was blocking at COX2 in different active site location compare to other ligands.…”
Section: Interactionmentioning
confidence: 57%
“…Inflammation that occurs in the body is correlated with inflammatory mediators such as COX-2. COX-2 has the function of initiating and maintaining physiological conditions during inflammation [11]. Compare to affinity character between chlorogenic acid and COX-2 in this research indicated that interaction was blocking at COX2 in different active site location compare to other ligands.…”
Section: Interactionmentioning
confidence: 57%
“…It is also known that silico molecular docking phytocompounds such as eriodyctiol, epicatechin, scutellarin, and ginkgolide A can bind to VEGF with tremendous energy as standard drugs for the 4T1 mammary carcinoma cell line [29,30]. We determined that the binding of eugenol and quercetin to VEGF resulted from the interaction of conventional hydrogen bonds and Pi-cation, Pi-sigma, and Pi-alkyl interactions, which significantly contributed to the stability of the bond structure [31][32][33][34]. Moreover, the binding interaction also supported the hydrogen's donor and acceptor abilities and thus may predict the antioxidant activity of quercetin and eugenol [16,35].…”
Section: Discussionmentioning
confidence: 98%
“…Docking of the receptor and small molecular ligand was performed using AutoDock Vina 1.1.2 [ 29 ]. The 2D complex and interactions of the docked ligand and receptor were analyzed using Discovery Studio Visualizer Version Client [ 30 ]. Affinity scores were used to evaluate the binding potential between the top four core targets and CUR.…”
Section: Methodsmentioning
confidence: 99%